Mechanical effects coupled with calcium waves - Kaźmierczak, B.; Dyzma, M. (Archives of Mechanics, 2010)
In the paper we find explicit formulae for heteroclinic travelling wave solutions in the system of equations describing the dynamics of cytosolic calcium concentration and the accompanying mechanical phenomena.